Performance evaluation of bridgeless isolated SEPIC-Luo converter for EV battery charging using PI and ANN controller - Dhandapani, Meena; Ravichandran, Padmathilagam; Shanmugam, Arulvizhi; Pachaivanan, Nammalvar (Institute of Advanced Engineering and Science, 2024)
Electric vehicle (EV) rechargeable battery packs that employ traditional power factor correction (PFC) circuit design have performance limitations due to their substantial conductivity loss that ensures at the input of a diode bridge rectifier (DBR). This study suggests a bridgeless (BL) isolated single ended primary inductance converter (SEPIC) - Luo converter to address the problem. As a result, the input current exhibits a power factor operation of unity throughout the charging process. DBR elimination and current conduction through a remarkably small number of circuits both significantly reduce conduction losses. The use of an artificial neural network (ANN) and proportional integral (PI) controller enhances the converter's performance with a stable DC link voltage. The suggested converter overall operation is thoroughly described in terms of variety of operating modes and simulation-based effectiveness. Here, with the assistance of the hysteresis current controller (HCC), the input current disruptions are reduced. Constant current and voltage management is used to successfully charge the EV battery, resulting in improved efficacy and inherent PFC. By utilizing simulation outcomes achieved from MATLAB, the performance of proposed BL isolated SEPIC-Luo in boosting the power quality of EV charger system is examined.